Influence of Sn content on the hydrogenation of crotonaldehyde catalysed by colloidally prepared PtSn nanoparticles. Issue 42 (30th March 2015) - Altmann, Lena; Wang, Xiaodong; Borchert, Holger; Kolny-Olesiak, Joanna; Zielasek, Volkmar; Parisi, Jürgen; Kunz, Sebastian; Bäumer, Marcus
Abstract : For increasing tin concentrations PtSn nanoparticles of similar size show a monotonically increasing selectivity towards crotylalcohol and a volcano like activity. Abstract : Bimetallic PtSn nanoparticles (NPs) of well-defined size and metal composition were prepared by means of colloidal methods. The mean particle diameter was about 2 nm for all samples irrespective of the Pt/Sn-ratio, which enables a systematic study of the influence of the composition on the catalytic properties while excluding particle size effects. The hydrogenation of crotonaldehyde was investigated as a reaction for which chemoselectivity is known to be a challenging task. Already very low atomic Sn contents (≈10%) were found to lead to a significantly improved activity which may be attributed to an electronic effect of Sn on Pt. For further increasing tin contents the activity decreased gradually. This trend was accompanied by a steady increase in selectivity towards the desired product (crotylalcohol). The results show that the highest crotylalcohol time yields can be obtained by using catalysts with an atomic Sn content of approximately 23%. In contrast, maximum crotylalcohol selectivities are achieved by using catalysts with a high tin content (>50%).